Establishing a Breastfeeding Consortium for Clinicians in Pediatric Outpatient Care. Issue 1 (January 2023) - Conover, Nicole; Vanderpool, Jill; Ginsberg, Julie; Kawan, Meg; Spatz, Diane L.
Abstract: Creating a supportive environment for breastfeeding mothers in the primary care setting has been shown to improve breastfeeding rates and duration. An important aspect of establishing a breastfeeding-friendly practice is to engage and educate health care providers. To increase consistency of breastfeeding care and interventions across a large primary care network, we established an Ambulatory Breastfeeding Consortium (ABC) focused on information sharing and discussion centered on care of breastfeeding and lactating families. The COVID-19 pandemic further highlighted the need to share up-to-date education and guidance, and the importance of the role of primary care providers in breastfeeding support. The ABC has been effective in engaging primary care nurses and other clinicians and disseminating information while encouraging discussion on the importance of providing informed care to breastfeeding families. Although more breastfeeding-specific education is recommended for clinicians, the ABC serves as a model for primary care clinicians to improve their knowledge and provide support for families through education, shared experience, and awareness across many pediatric primary care network sites. Abstract : Development of a breastfeeding consortium for ambulatory care clinics in the Children's Hospital of Philadephia primary care network including 31 sites across Pennsylvania and New Jersey is presented. Virtual monthly meetings and education facililtated clinicians knowledge on various breastfeeding topics. The consortium has been especially helpful during the COVID-19 pandemic as birthing hospitals discharge new mothers ealier than usual and often without full assessment of the breastfeeding couplet. Ongoing updates of information from the government and professional organizations were able to be shared with members of the interdisciplinary team.